Implementação de mapas elastográficos utilizando filtro mediano em uma plataforma de arquitetura aberta - Carbente, Rubem Petry (2019)
The use of ultrafast technology has allowed to observe phenomena and events in the ultrasonography: among them the obtaining of the map of micro Doppler and the evaluation of the viscoelasticity of the tissue. Ultrafast image formation can be utilized to find transitory shear waves propagating in soft tissue, which permits quantification of the mechanical properties of the tissue via elastography. This technique permits simple and noninvasive diagnosis and monitoring of disease. This article presents a method to estimate the viscoelastic properties and rigidity of structures using the ultrasound technique known as shear wave elasticity imaging (SWEI). The Verasonics Vantage 128 research platform and L11-4v transducer were used to acquire radio frequency signals from a model 049A elastography phantom (CIRS, USA), with subsequent processing and analysis in MATLAB. The images and indexes obtained reflect the qualitative measurements of the different regions of inclusions in the phantom and the respective alterations in the viscoelastic properties of distinct areas. Comparison of the results obtained with this proposed technique and other commonly used techniques demonstrates the characteristics of median filtering in smoothing variations in velocity to form elastographic images. The results of the technique proposed in this study are within the error margins indicated by the phantom manufacturer; for the phantom base and for inclusions type I, II, III and IV, the elasticity in kPa and the percentage errors obtained by the method proposed in this study were of 29.18 (-16.7%), 10.26 (-28.2%), 15.64 (-11.7%), 45.81 (-1.8%), and 85.21 (-6.5%), respectively. The new technique to obtain images uses a distinct filtering function which considers the mean velocity in the region around each pixel, in turn allowing adjustments according to the characteristics of the phantom inclusions within the ultrasound and optimizing the resulting elastographic images.